Optimization of pressure parboiling conditions and pre-conditioned moisture content of brown rice (unpolished rice) for microwave puffing and its comparison with hot sand bed puffing - Ajay Kumar Swarnakar; Prem Prakash Srivastav; Susanta Kumar Das (International Journal of Food Studies)
Brown rice puffing (unpolished rice) gives a more nutritious product compared to traditional puffed polished rice and reduces the cost of the product significantly, even though, the rice bran layer resists expansion during puffing. In the present study, brown rice was puffed in a microwave and hot-sand-bed after its pressure parboiling. Pressure parboiling parameters, steam pressure (196, 294, 392, 490 kPa) and steaming time (5, 10, 15 min), along with pre-conditioned moisture content (8, 10, 12 % wb) were studied and optimized for puffing characteristics (puffing percentage, expansion ratio, whiteness index, bulk density and hardness). All the experiments were carried out using a full factorial design. Statistical analysis showed there was a significant effect of processing variables on puffing characteristics. Optimized steam pressure, steaming time and pre-conditioned moisture content for microwave puffing were found to be 303.6 kPa, 14.25 min and 11.6% (wb) respectively, and for hot-sand-bed puffing to be 260.7 kPa, 15 min and 8% (wb) respectively.